The analysis of the problems on binding energy within the proton-proton fusion of a deuteron and on definition of the spins of nuclei and nuclear leptons - Skibinskyi, L. P.; Petruk, V. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
This analysis has resulted in a conclusion that the proton-proton fusion of deuteron should be accompanied by radiation of gamma-photon of 1,6 МeV (the binding energy), that this reaction in the course of light deuteron with the energy of rest 1874,35 МеV is formed, and its structure should include light stable neutron with the energy of rest 938,2796 МeV, and electrons and positron are particle with quantization spins and magnetic moments, they are included into the structure of nucleons, form their charges and magnetic moments and take part in strong interaction. That has brought to the solution of the problem of determination of the spins of nucleuses, nuclear leptons, opening the process of duplication of light neutrons with gamma-photon at proton-neutron fusion (PNF) of light deuterons in hydrogen and the opportunity to create PNF reactors, both fusion of light and average nuclei on slow protons